Content Delivery Readiness of Philippine Higher Education Institution Websites: Evidence from HTTP Archive and Chrome UX Report (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the content delivery readiness of selected Philippine Higher Education Institution websites using public performance data from the Chrome User Experience Report (CrUX) and HTTP Archive. The study covered 30 official website origins, consisting of 10 State Universities and Colleges, 10 private HEIs, and 10 Local Universities and Colleges. Each website was validated and normalized before data extraction. CrUX data for May 2026 and HTTP Archive page-level data from the May 1, 2026 crawl were collected through BigQuery. Of the 30 websites, 25 had complete data from both sources, four had CrUX data only, and one had no usable match. The readiness framework combined field indicators related to actual user experience with page-level indicators describing technical delivery conditions. Among the 25 complete-data websites, five showed high readiness, 13 moderate readiness, and seven low readiness. Private HEIs recorded the highest average score among the three groups, although the comparison was interpreted descriptively because the corpus was purposively selected. The most common issues were heavy page weight, slow visual loading, high request count, slow Time to First Byte, and slow Largest Contentful Paint. Sensitivity testing using three alternative weighting schemes showed that 84 percent to 96 percent of classifications remained unchanged, while rank correlations ranged from 0.962 to 0.980. These results indicate that the main findings remained generally stable across the alternative models, with most category changes occurring near the score boundaries. The resulting framework provides a practical basis for identifying and prioritizing improvements in payload size, loading behavior, request management, server response, and routine website performance monitoring.